A novel 2D porous C₃N₂ framework as a promising anode material with ultra-high specific capacity for lithium-ion batteries - Cai, Xinyong (2022)
Lithium-ion batteries (LIBs) are among the most promising and widely deployed energy storage sources, however, the lack of high capacity anode materials is a critical challenge to advancing LIBs for high energy storage applications. Two-dimensional (2D) porous carbon nitride frameworks based on C-N scaffolds and ordered pores have provided a promising source for developing high-capacity LIB anode materials. Using swarm-intelligence 2D global minimum structure-search methods, in conjunction with structure design via the assembly of organic unit building blocks, we identified a novel holey α-C3N2 monolayer, which has a crystalline ordered-porous framework and higher N content than the known holey C2N monolayer. In the α-C3N2 framework, the enhanced N content and high porosity provide multiple pyridinic-N sites, thus resulting in more Li adsorption sites, and consequently an extremely high theoretical capacity (∼2791 mA h g−1). Meanwhile, this porous α-C3N2 monolayer was found to possess a low Li-diffusion energy barrier, suitable open-circuit voltage, and high feasibility for experimental realization. These characteristics make the α-C3N2 monolayer a highly promising anode material for LIBs. Moreover, our finding the α-C3N2 framework can be further extended and several derivatives can be constructed to maintain high Li storage capacity, which reveals that the porous C-N frameworks with multiple pyridinic-N sites are a promising class of anode materials for high-capacity LIBs. This finding further offers a new avenue to guide the design of new holey C-N materials with a high capacity for energy storage applications.